J. Basanavičius’ relations with USA editor A. Milukas - Gargasaitė, Dalia (Knygotyra, 1992)
In the article, the relations of the famous scientist and folklore expert J. Basanavičius with USA editor of Lithuanian origin, priest A. Milukas, are brought to light. Through his efforts, four books by J. Basanavičius were printed in the USA—collections of folklore compositions. They are still of great scientific value.